2001
DOI: 10.1002/ajmg.1209
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genome screen of panic disorder and anxiety disorder proneness using homology to murine QTL regions

Abstract: Family and twin studies have indicated that genes influence susceptibility to panic and phobic anxiety disorders, but the location of the genes involved remains unknown. Animal models can simplify gene-mapping efforts by overcoming problems that complicate human pedigree studies including genetic heterogeneity and high phenocopy rates. Homology between rodent and human genomes can be exploited to map human genes underlying complex traits. We used regions identified by quantitative trait locus (QTL)-mapping of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 68 publications
1
63
0
Order By: Relevance
“…Linkage analyses of PD have implicated several chromosomal regions including 1q, 8 2q, 9 7p, 10,11 9q, 12 12q, 13 13q, 14,15 15q 9 and 22q. 15 In association analyses, candidate genes including HTR 1A, 16 2A, 17,18 CCK, 19 ADORA2A, 20 MAOA 21 and COMT 22,23 have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage analyses of PD have implicated several chromosomal regions including 1q, 8 2q, 9 7p, 10,11 9q, 12 12q, 13 13q, 14,15 15q 9 and 22q. 15 In association analyses, candidate genes including HTR 1A, 16 2A, 17,18 CCK, 19 ADORA2A, 20 MAOA 21 and COMT 22,23 have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Several genome-wide linkage studies have tried to identify genomic regions harboring quantitative trait loci (QTLs) that influence the vulnerability for anxiety disorders. All these studies [6][7][8][9][10][11][12][13][14][15] ascertained the pedigrees through probands with panic disorder, except for one study 16 that included pedigrees with at least one member having an anxiety disorder or somatoform pain. Panic disorder is the most frequently analyzed phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Panic disorder is the most frequently analyzed phenotype. [6][7][8]13,14 Two studies focused on panic disorder with comorbid medical conditions, that is renal/ bladder conditions, thyroid irregularities, mitral valve prolapse and severe headaches. 11,15 Simple phobia and social phobia have each been investigated once.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The region also overlaps a suggestive linkage from the Kaabi et al 22 PD study included herein as well as a locus identified in a targeted linkage scan performed in a single, large pedigree segregating PD and risk for early-onset ANX. 38 Surprisingly, there was no evidence in the 8p22, a region with replicated linkage to harm avoidance, another anxiety-related trait. 39 …”
Section: Neuroticismmentioning
confidence: 99%